Answer :


Proof:


Take LHS:



Identities used:


cos 2x = cos2 x – sin2 x



sin 2x = 2 sin x cos x



Therefore,




{ a2 – b2 = (a - b)(a + b) & sin2 x + cos2 x = 1}



{ a2 + b2 + 2ab = (a + b)2}





Multiplying numerator and denominator by







{ sin (A – B) = sin A cos B – sin B cos A


cos (A – B) = cos A cos B + sin A sin B}




= RHS


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

0 ≤ x ≤ π aRD Sharma - Mathematics

Prove that:RD Sharma - Mathematics